2015
DOI: 10.1016/j.ijantimicag.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Assessing phage therapy against Pseudomonas aeruginosa using a Galleria mellonella infection model

Abstract: The Galleria mellonella infection model was used to assess the in vivo efficacy of phage therapy against laboratory and clinical strains of Pseudomonas aeruginosa. In a first series of experiments, Galleria were infected with the laboratory strain P. aeruginosa PAO1 and were treated with varying multiplicity of infection (MOI) of phages either 2h post-infection (treatment) or 2h pre-infection (prevention) via injection into the haemolymph. To address the kinetics of infection, larvae were bled over a period of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
41
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 18 publications
8
41
2
3
Order By: Relevance
“…Although previous work reported the inoculation of bacteria/phages by intrahaemocoelic injection (Abbasifar et al, 2014; Beeton et al, 2015), we found ingestion via the oral route more efficient at inducing colonization and producing reproducible therapy results. The observed higher efficacy of the phages when used prophylactically rather than with remedial treatment is consistent with a previous report (Beeton et al, 2015). Interestingly, the best treatment was observed when vancomycin was given prophylactically followed by phage application.…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…Although previous work reported the inoculation of bacteria/phages by intrahaemocoelic injection (Abbasifar et al, 2014; Beeton et al, 2015), we found ingestion via the oral route more efficient at inducing colonization and producing reproducible therapy results. The observed higher efficacy of the phages when used prophylactically rather than with remedial treatment is consistent with a previous report (Beeton et al, 2015). Interestingly, the best treatment was observed when vancomycin was given prophylactically followed by phage application.…”
Section: Discussioncontrasting
confidence: 73%
“…Although the insect is used as an infection model for various pathogens (Mukherjee et al, 2010; Ramarao et al, 2012; Hill et al, 2014; Beeton et al, 2015) and antimicrobial testing (Seed and Dennis, 2009; Abbasifar et al, 2014; Beeton et al, 2015; Olszak et al, 2015), to our knowledge this report is the first published data to describe its use to study C. difficile colonization and phage treatment. We established that 10 5 C. difficile cells were sufficient for colonization to occur in the larvae and to cause the first and total mortality at 24 and 60 h respectively post-infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that P. aeruginosa is becoming resistant to most antibiotics, a common infection may be fatal. Therefore, the feasibility of treating bacterial infections with bacteriophages has been extensively studied2728293031. Several studies have reported the efficacy of phage therapy against P. aeruginosa .…”
Section: Resultsmentioning
confidence: 99%